(untitled) (Orfeu, 2017)
The concept of melodic fluency is considered today an important one in Schenkerian theory. William Pastille (1990:71-72) shows that this notion, first presented in the first volume of Counterpoint, initiated the development of the Ursatz concept. The knowledge of the principle of melodic fluency, he adds, affords two abilities: “the ability to uncover long-range melodic motions and the ability to reveal underlying contrapuntal patterns”, which “became the mainstays of his analytical approach.” Allen Cadwallader and William Pastille (1992:120) confirm that Schenker “formally introduced” the concept of melodic fluency in Counterpoint I, and define it as “essentially a name for good voice leading in strict counterpoint”. William Rothstein, who defines Schenker’s concept of melodic fluency as a “stepwise continuity in the upper voice” (1991:292), makes it an essential element of his description of “implied tones”, when a conjunct tone is implied in an apparently leaping melodic line.